3D CHARACTERIZATION OF WOOD BASED FIBROUS MATERIALS: AN APPLICATION - Lux, Jérôme; Delisée, Christine; Thibault, Xavier (Image Analysis and Stereology, 2011)
Morphological characterization of wood based fibrous materials is carried out using X-ray tomography. This technique allows the non destructive observation at the scales of a fibre (microscopic scale) and of a network of fibres (mesoscopic scale). The 3D images are processed using classical tools of mathematical morphology. Measures of porosities and estimations of the size distributions of fibres and pores are carried out and compared to other results. An alternative method for the calculation of the local orientation of the fibres is also described to quantify the anisotropy of the fibres network. Finally, the individualization of the fibres is obtained from the representation of the fibrous network as a 3D skeleton, making possible further measurements on the isolated fibres.